ANALISIS PENURUNAN DAN DEFLEKSI PONDASI BORED PILE PADA WILAYAH KOTA TIMUR GORONTALO - Dwianto; Aristi Ayuningsi Ode Asri (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Negeri Gorontalo, 2026)
The foundation is a critical structural element that must safely transfer axial and lateral loads from a building to the supporting soil. Due to the variable bearing capacity of sandy soils across East City District, Gorontalo, general design correlations are often unreliable, making site-specific verification necessary. This study analyzes the axial settlement and lateral deflection of bored pile foundations for a Bank Indonesia branch office construction project in East City, Gorontalo, by comparing analytical methods (Poulos and Davis for settlement, Broms for lateral deflection), Plaxis 2D numerical modeling, and field loading tests. Results show the pile's axial bearing capacity reached 1,025.15 kN, producing a maximum settlement of 3.04 mm. Under a design load variation of 850 kN, settlement values were 2.5 mm (Poulos and Davis), 1.92 mm (Plaxis), and 2.03 mm (field test), with an average difference of 16.89%, indicating good agreement between analytical and field results for axial behavior in sandy soil. For lateral behavior, the maximum allowable lateral load was 114.99 kN, exceeding McNulty's required criterion, so no batter piles were needed. Lateral deflection analysis produced 5.49 mm under a 50 kN design load, compared to only 1.4 mm from the field lateral loading test, an average difference of 77%, both remaining below McNulty's 6 mm allowable limit. The much larger discrepancy in lateral deflection indicates that the conventional Broms method is considerably more conservative than actual field behavior. Overall, the bored pile foundation performed well within allowable limits, and the percentage differences obtained may serve as correction factors for future pile foundation designs in similar sandy soil conditions in Gorontalo, particularly where field test data are limited.